2017
DOI: 10.1590/1517-869220172305163582
|View full text |Cite
|
Sign up to set email alerts
|

Tempo De Tela, Percepção Da Qualidade De Sono E Episódios De Parassonia Em Adolescentes

Abstract: Introdução: O sono é um importante componente no processo de desenvolvimento biológico e mental das crianças e dos adolescentes, considerado fonte de revitalização das funções orgânicas. Objetivo: Analisar a associação entre o tipo e tempo de exposição à tela, a percepção da qualidade de sono e os episódios de parassonia em adolescentes. Métodos: Estudo transversal que incorpora um levantamento epidemiológico de base escolar com amostra representativa (n = 481) de estudantes (14 a 19 anos) do ensino médio da r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
11
0
9
Order By: Relevance
“…This finding is similar to that of Hoefelmann et al [31] who found 45.7% of 14-24-year-olds had poor sleep quality. Explanations for this high prevalence may be related to biological, social, and behavioral factors such as age, economic class, physical inactivity, screen time, school activities, caffeine intake, and chronic diseases [9,10,[32][33][34][35].Despite the considerable coffee consumption among the studied adolescents and evidence that high and moderate caffeine consumption is associated with sleep disorders in adolescents [36,37], there was no significant difference in coffee consumption between the groups of good and poor sleepers.…”
Section: Discussionmentioning
confidence: 84%
“…This finding is similar to that of Hoefelmann et al [31] who found 45.7% of 14-24-year-olds had poor sleep quality. Explanations for this high prevalence may be related to biological, social, and behavioral factors such as age, economic class, physical inactivity, screen time, school activities, caffeine intake, and chronic diseases [9,10,[32][33][34][35].Despite the considerable coffee consumption among the studied adolescents and evidence that high and moderate caffeine consumption is associated with sleep disorders in adolescents [36,37], there was no significant difference in coffee consumption between the groups of good and poor sleepers.…”
Section: Discussionmentioning
confidence: 84%
“…14 The proportion of negative perception of sleep quality in the present study was also lower than that of foreign countries 12,25 and other Brazilian regions. 1,15 A probable explanation for this variability in the results is the fact that adolescent sleep is influenced by socioeconomic, cultural and behavioral differences, which seem to be decisive in altering the duration and quality of sleep in adolescents. 2,14 Differences in sample characteristics should also be considered, since, in this study, about 60% of adolescents were aged up to 11 years old.…”
Section: Discussionmentioning
confidence: 99%
“…This was different from the other studies in which the age range age ranged from 14 to 19 years old. 2,10,14,15,26 Older teenagers have more freedom to manage their time with friends, participate in leisure activities until late hours, and socialize more frequently and for longer on electronic devices, 17 which can contribute to inadequate sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations